2014
DOI: 10.3109/13685538.2014.908281
|View full text |Cite
|
Sign up to set email alerts
|

Urea to creatinine ratio: a forgotten marker of poor nutritional state in patients undergoing hemodialysis treatment

Abstract: In addition to routinely used markers of malnutrition UCR may provide additional information regarding malnutrition in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 30 publications
(31 reference statements)
2
18
5
Order By: Relevance
“…A high fever and high CRP level might reflect the extent of inflammation . Meanwhile, the value of BUN is not clear, but we presume that it indicates dehydration, renal dysfunction and increased catabolism, which might have the negative impact of aggravating the infection.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A high fever and high CRP level might reflect the extent of inflammation . Meanwhile, the value of BUN is not clear, but we presume that it indicates dehydration, renal dysfunction and increased catabolism, which might have the negative impact of aggravating the infection.…”
Section: Discussionmentioning
confidence: 89%
“…13,14 A high fever and high CRP level might reflect the extent of inflammation. 15 Meanwhile, the value of BUN is not clear, but we presume that it indicates dehydration, 16 renal dysfunction and increased catabolism, 17 which might have the negative impact of aggravating the infection. The CURB-65 pneumonia severity score is one of the main scoring systems for evaluating the risk of mortality with CAP.…”
Section: Discussionmentioning
confidence: 91%
“…While obesity is a risk factor for the progression of disease in hemodialysis patients, malnutrition is related to increased morbidity and mortality rates. Hemodialysis is associated with increased energy and protein requirements [8]. Hemodialysis patients are often exposed to a number of dietary restrictions related to dietary phosphorus, potassium, sodium, fluid intake, and macronutrients, including carbohydrate and fat [10].…”
Section: Discussionmentioning
confidence: 99%
“…Adverse changes in fluid-electrolyte balance (hyperkalemia, hyperphosphatemia, peripheral and pulmonary edema) can be seen in patients who do not comply with their diet. The purpose of dietary therapy for patients undergoing hemodialysis treatment is to provide an optimal nutritional status and prevent malnutrition without disturbing the fluid-electrolyte balance or increasing uremic symptoms [8]. Consumptions of excessive fat, excessive salt or insufficient fiber may lead to atherogenic results in dialysis patients.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, we did not assess fluid/volume status in our cohort and therefore could not differentiate which stimulus may have been most important in increasing copeptin levels in patients with elevated NRS scores [18] . A study conducted by Tufan et al [19] found that in addition to routinely used markers of malnutrition, the urea/creatinine ratio may provide additional information on malnutrition in a population of hemodialysis patients. Our findings indicating significant association of malnutrition with urea but not with creatinine support that hypothesis.…”
Section: Perspectives From Other Studiesmentioning
confidence: 99%